Overview of Operational Global and Regional Ocean Colour Essential Ocean Variables Within the Copernicus Marine Service - Vittorio E. Brando; Rosalia Santoleri; Simone Colella; Gianluca Volpe; Annalisa Di Cicco; Michela Sammartino; Luis González Vilas; Chiara Lapucci; Emanuele Böhm; Maria Laura Zoffoli; Claudia Cesarini; Vega Forneris; et al. (Remote Sensing)
The Ocean Colour Thematic Assembly Centre (OCTAC) of the Copernicus Marine Service delivers state-of-the-art Ocean Colour core products for both global oceans and European seas, derived from multiple satellite missions. Since 2015, the OCTAC has provided global and regional high-level merged products that offer value-added information not directly available from space agencies. This is achieved by integrating observations from various missions, resulting in homogenized, inter-calibrated datasets with broader spatial coverage than single-sensor data streams. OCTAC enhanced continuously the basin-level accuracy of essential ocean variables (EOVs) across the global ocean and European regional seas, including the Atlantic, Arctic, Baltic, Mediterranean, and Black seas. From 2019 onwards, new EOVs have been introduced, focusing on phytoplankton functional groups, community structure, and primary production. This paper provides an overview of the evolution of the OCTAC catalogue from 2015 to date, evaluates the accuracy of global and regional products, and outlines plans for future product development.